ISU KESEHATAN DALAM SENGKETA IMPOR DAGING AYAM ANTARA INDONESIA-BRAZIL DI WTO - Siswanto, Ari (Universitas Brawijaya, 2021)
AbstractThis paper discusses the issue of human health protection as one of the exceptions of GATT obligations, considering the elements in Article XX (b) of GATT are still general in nature and thus have the potential to bring different interpretation. Focusing on the elements of